GAMBARAN FAKTOR RISIKO DAN TERAPI MEDIKAMENTOSA PADA PASIEN OTITIS MEDIA SUPURATIF KRONIK TANPA KOLESTEATOMA DI RUMAH SAKIT HAJI MINA MEDAN TAHUN 2015 HINGGA 2019 - NURUL FITRIA UTAMI; MUHAMMAD EDY SYAHPUTRA NASUTION (JURNAL ILMIAH MAKSITEK, 2021)
The incidence of chronic suppurative otitis media (CSOM) in developing countries is very high compared to developedcountries. This is due to inadequate hygiene, socioeconomic factors, recurrent respiratory infections, as well as communitymisunderstanding of this disease so that they do not go to treatment completely. The aim is to describe the risk factors andmedical therapy in CSOM patients without cholesteatoma at the Medan Haji Mina Hospital from 2015 to 2019. Descriptive,which describes the condition of a problem in accordance with what happened at the Medan Haji Mina Hospital. It was foundthat the most antibiotic drug use was quinolone, namely 30 people (60%), then the symptomatic therapy that was mostlygiven was 30 people (60%) given topical hydrogen peroxide. It was found that the most widely used antibiotic was thequinolone class and the most commonly used symptomatic therapy was topical hydrogen peroxide.